(untitled) (Economic studies journal, 2018)
This study investigates if some empirical evidence exists either supporting a substitution or a complementary relationship between inward foreign direct investment and exports in Sudan. With this aim, an aggregate data (seasonal adjusted) from the Sudanese economy covering the period(01:2007-0:2016). A vector error correction model was employed to show the strength and direction of causal relationships through the dynamic variance decomposition and the impulse response approach. The results provide evidence of a positive bilateral log – term Granger causality between foreign direct investment and exports.